Relation of Cholelithiasis and Body Mass Index among Different Age Groups - Yadav, Umesh Kumar; Bhatta, Pashupati; Raya, Akash; Aryal, Vibina (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Cholelithiasis is a common presentation in the department of surgery. One of the potential risk factors of cholelithiasis is obesity, which is a common problem faced by most adult population. The aim of this study is to see the association of cholelithiasis with body mass index among different age groups. MATERIAL AND METHODS This cross-sectional study was done in the Department of General Surgery of National Medical College, Birgunj. Ethical clearance (Ref. F-NMC/565/078-079) was obtained from the institutional review committee. Total of 75 subjects were included in the study. Subjects presenting with cholelithiasis in the out-patient department of Surgery were included in the study. Height and weight of the subjects were recorded along with age and other parameters. Body mass index (BMI) was calculated using the Quetelet’s formula, weight in kg/ height in m2. The body mass index was than categorized according to World Health Organization. RESULTS The mean age of the total participants was 43.85±11.82 years. The mean BMI was 25.81±9.95 kg/m2. Among the age group 20 – 35 years 30% were overweight and 15% were obese where as in age group 36 – 50 years 44.4 % were overweight and 11.2 % were obese. Similarly in participants above 50 years 32.1% were overweight and only 3.6% were obese. CONCLUSION Cholelithiasis is one of the common surgical problems. Number of patients with gallstones increases with increasing age. In this study, more number patients are seen with normal BMI. However, higher number of patients are found having overweight or obesity in the age group of 36-50 years.